Estimation of J-resistance curves of SA-508 steel from small sized specimens with the correction of crack tip constraint. (September 2018) - He, G.W.; Bao, C.; Cai, L.X.; Wu, Y.J.; Zhao, X.H.
Highlights: Two small-sized specimens are proposed for fracture toughness test. J - Q - M principle used to approximately quantify the 3D crack-tip constraint. Constraint corrected J-R curves of SA508 steel have been obtained. J-R curves of actual components can be predicted in structural integrity assessment. Abstract: Based on normalization method, experimental J -resistance ( J-R ) curves of SA-508 steel using five types of specimen configurations, such as C-shaped outside edge-notched compression (COEC), C-shaped inside edge-notched tension (CIET), miniature single edge notched bend (Mini-SENB), standard SENB and compact tension (CT) specimens are given. Great difference can be observed in these experimental J-R curves because of the various specimen configuration and dimension. The results show that, COEC specimens present the lowest J-R curves with high level of crack tip constraint, but the highest J-R curves are estimated from Mini-SENB specimens because of the lowest level of crack tip constraint they have. The classic crack tip constraint effect can explain these differences, so J-Q-M theory is applied to quantify this effect through 3D elastic plastic finite element analysis, and a family of constraint corrected J-R curves for SA-508 steel are consequently obtained, which match well with the experimental data for five types of specimen configurations with different dimensions. It is applicable to predict the J-R curves of actual cracked components as long as the crack tip constraint is determined.